Analisis Matematika Pada Pembuatan Rumah Panggung Toraja - Syafruddin Side; Sukarna; Jusriadi (Jurusan Matematika FMIPA UNM, 2020)
Geometry is branch of science that learning about the relationship between points, lines, sides , plane figure and solid figure. The application of geometry mathematics is very helpful in daily life. For example, the determination of tower height by using sunlight where in its determination can use the comparison system. Then, determine the distance or width of the river without measuring it manually, that is by using the help points and lines that are congruent. The aim of this research is finding out how the results of the application of mathematics in building Toraja Traditional house. The analysis process is done by observation, interview and documentation to see the process of building Toraja Traditional house. Based on the results of data analysis that is obtained, it was find the sequences pattern on the poles or beams in each type of house. Then the method of using parallel lines, lines extension and similarity on the roof of the house. Mathematics application can be applied in Toraja Traditional house by using parabolic equations and parabolic functions in determining the curvature of house roof.